A Versatile C–H Halogenation Strategy for Indole Derivatives under Electrochemical Catalyst‐ and Oxidant‐Free Conditions. Issue 35 (8th May 2018) - Sun, Linhao; Zhang, Xing; Li, Zilong; Ma, Jimei; Zeng, Zhen; Jiang, Hong
Abstract : Halogenated indoles are essential structural motifs in bioactive natural products. Reported herein is an economical and scalable electrochemical protocol for regioselective 3C–H halogenation of indole derivatives. This strategy provides access to a host of 3‐iodo‐, 3‐bromo‐, 3‐chloro‐, and 3‐thiocyanoindole derivatives under mild conditions using inexpensive (pseudo)halide salts as the sole reagent. The optimized conditions do not require any supplementary electrolyte salts. Abstract : An economical and scalable electrochemical protocol for regioselective 3C–H halogenation of indole derivatives is reported. This strategy provides access to a host of 3‐iodo‐, 3‐bromo‐, 3‐chloro‐, and 3‐thiocyanoindole derivatives under mild conditions using inexpensive (pseudo)halide salts as the sole reagent. No supplementary electrolyte salt is necessary.